Beyond the things themselves economic aspects of the Italian race laws (1938-2018) - Pavan, Ilaria 1972- (Yad Vashem, 2019)
"Ilaria Pavan carefully analyzes the economic aspects of Jewish persecution and the community's struggle before, during, and after World War II. She exposes the persecutory intentions and mechanisms of the Italian regime and discusses the long series of provisions, decrees, and laws that severly afflicted the Jewish community." --Provided by the Publisher
Keywords: Geschichte 1945-1970; Geschichte 1938-1970; Geschichte 1938-1945; Wirtschaftsentwicklung; Juden; Arisierung; Wiedergutmachung; Rassengesetzgebung; Italien; World War, 1939-1945 / Jews / Italy; Jews / Legal status, laws, etc / Italy / History / 20th century; Italy / Ethnic relations / History / 20th century; Race discrimination / Law and legislation / Italy / History / 20th century; Holocaust, Jewish (1939-1945) / Economic aspects / Italy